2015
DOI: 10.1007/s00259-015-3288-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging with 124I in differentiated thyroid carcinoma: is PET/MRI superior to PET/CT?

Abstract: PET/MRI of the neck was found to be superior to PET/CT in detecting iodine-positive lesions. This was attributed to the higher sensitivity of the PET component, Although helpful in some cases, we found no substantial advantage of PET/MRI over PET/CT in categorizing iodine-positive lesions as either metastasis or thyroid remnant. Volume information provided by MRI for some iodine-positive lesions might be useful in dosimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…MR was performed simultaneously before and after administration of contrast medium (0.2 mL/kg body weight Dotarem; Guerbet GmbH, Sulzbach, Germany) using a head-and-neck coil. Attenuation correction was based on an automatically generated four-compartment model attenuation map (μ-map) derived from a two-point T1-W Dixon VIBE (volumetric interpolated breath-hold examination) sequence [ 12 ]. Standard corrections for random coincidence, scatter, and dead time were performed.…”
Section: Methodsmentioning
confidence: 99%
“…MR was performed simultaneously before and after administration of contrast medium (0.2 mL/kg body weight Dotarem; Guerbet GmbH, Sulzbach, Germany) using a head-and-neck coil. Attenuation correction was based on an automatically generated four-compartment model attenuation map (μ-map) derived from a two-point T1-W Dixon VIBE (volumetric interpolated breath-hold examination) sequence [ 12 ]. Standard corrections for random coincidence, scatter, and dead time were performed.…”
Section: Methodsmentioning
confidence: 99%
“…To date, studies regarding the efficacy of PET/MR in thyroid carcinoma have rarely been reported. Initially, Binse et al (19) reported that the detection rate of iodine-positive metastasis in PET/MR was superior to that in PET/CT. On the other hand, Dercle et al (20) reported that PET/MR does not show any advantage over PET/CT in detecting primary diseases of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…First, iodine natively has high affinity with thyroid tissue. Binse et al [ 13 ] clearly visualized metastatic lesions in patients with differentiated thyroid cancer (DTC) using 124 I and PET/CT or PET/MRI. PET imaging using 124 I will greatly contribute to the management of patients with high-risk DTC.…”
Section: Radionuclide—iodine-124mentioning
confidence: 99%